2011
DOI: 10.1111/j.1753-6405.2010.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the barriers preventing Indigenous Health Workers delivering tobacco interventions to their communities

Abstract: The general Australian population has experienced a steady decrease in smoking prevalence over the past 30 years to less than 20% in 2004 with a target set for less than 9% by 2020.1 Tobacco use in Indigenous Australians is disproportionately higher with approximately 51% of Indigenous men and 47% of Indigenous women reporting regular smoking.2 These high levels have changed little since the mid-1990s. 3 In some remote communities, for example, in Arnhem Land in the Northern Territory, a number of studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 13 publications
0
58
1
Order By: Relevance
“…The remaining four studies also referred to evidence among general populations and/or included studies which compared outcomes between Indigenous and non-Indigenous people [2124]. Specific sub-groups of populations that were reported as the focus of the reviews included pregnant women ( n  = 2) [25, 26], adolescents ( n  = 2) [27, 28], school students ( n  = 1) [28] and Aboriginal Health Workers ( n  = 1) [29]. Thirteen reviews included Indigenous people in any country, but only reported studies based in Australia, Canada, New Zealand, and the USA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining four studies also referred to evidence among general populations and/or included studies which compared outcomes between Indigenous and non-Indigenous people [2124]. Specific sub-groups of populations that were reported as the focus of the reviews included pregnant women ( n  = 2) [25, 26], adolescents ( n  = 2) [27, 28], school students ( n  = 1) [28] and Aboriginal Health Workers ( n  = 1) [29]. Thirteen reviews included Indigenous people in any country, but only reported studies based in Australia, Canada, New Zealand, and the USA.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term, broad approaches are needed to de-normalise smoking in Indigenous communities as social norms and stressors perpetuate tobacco use in pregnancy. There is lack of knowledge of smoking harms and inadequate salience of current antismoking messages for maternal smokers, as well as poor knowledge of, access to, and use of evidence-based treatments for smoking cessation in pregnancy.Thompson 2011 [29](Unclear)Moderate‘A review of the barriers preventing Indigenous Health Workers delivering tobacco interventions to their communities’Australian (health workers only)Impact of smoking status on provision of tobacco information.14Non-randomised [3]Qualitative [8]Reviews [3]Mainly qualitative statementsSmoking cessation: Reports 9% quit rate; Relapse related to stressful times in clients lives.Knowledge/practice/workforce capability: Degree smoking information delivered may depend on IHWs’ tobacco use. Non-smoking IHWs more likely than smokers to talk to community about smoking (1 study) and smoking was barrier to giving support and/or information to community (1 study).…”
Section: Methodsmentioning
confidence: 99%
“…Good evidence exists for efficacy of advice from doctors and nurses [22, 23], however midwives, including midwives caring for Indigenous women, have expressed reluctance to address smoking, concerned that they may damage their relationship with their clients [12, 24]. Similar concerns have been expressed by AHWs, with the additional concern that AHW smoking may impede providing advice [25]. However, over half the women in our study indicated that support from each of the health professionals was likely to be helpful, suggesting this approach is acceptable, perceived to be effective and may be a fruitful approach.…”
Section: Discussionmentioning
confidence: 99%
“…1 Aboriginal Health Workers (AHWs) have a pivotal role in addressing the high smoking prevalence in Aboriginal communities; however, AHWs' own smoking may be a barrier preventing them from providing quit support and/or information to their communities. 2 This letter presents the results of a study that aimed to determine the proportion of Aboriginal health students (AHS) enrolled at an Aboriginal Training College who were current smokers, their smoking attitudes and quitting issues, and their interest in a Quit smoking program. Participation involved completing a written survey.…”
mentioning
confidence: 99%
“…Water fluoridation is widely accepted as the most effective, costeffective, equitable and safe means of protection from tooth decay. 1,2 Changing oral hygiene habits, food and drink consumption and fluoride exposure are reasons to call for updated evidence of the continued benefit of water fluoridation into the 21 st century. In 2007, children's dental health was compared across fluoridated and non-fluoridated regions on the NSW Central Coast in an ecological cross-sectional study.…”
mentioning
confidence: 99%